2010
DOI: 10.1159/000289569
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Secretion by Neuroendocrine Tumor Cells Is Inhibited by Octreotide and by Inhibitors of the PI3K/AKT/mTOR Pathway

Abstract: Gastroenteropancreatic (GEP) endocrine tumors are hypervascular tumors able to synthesize and secrete high amounts of VEGF. We aimed to study the regulation of VEGF production in GEP endocrine tumors and to test whether some of the drugs currently used in their treatment, such as so- matostatin analogues and mTOR inhibitors, may interfere with VEGF secretion. We therefore analyzed the effects of the somatostatin analogue octreotide, the mTOR inhibitor rapamycin, the PI3K inhibitor LY294002, the MEK1 inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 110 publications
4
64
0
1
Order By: Relevance
“…In fact, a positive relationship between FLNA and vascular endothelial growth factor (VEGF) was found in patients with lung cancer (Uramoto et al 2010), suggesting that FLNA is implicated in angiogenesis through links with VEGF. Interestingly, it has been demonstrated that VEGF pathway is overexpressed in neuroendocrine tumours (Ö berg et al 2013), this pathway being inhibited by somatostatin analogues (Villaume et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a positive relationship between FLNA and vascular endothelial growth factor (VEGF) was found in patients with lung cancer (Uramoto et al 2010), suggesting that FLNA is implicated in angiogenesis through links with VEGF. Interestingly, it has been demonstrated that VEGF pathway is overexpressed in neuroendocrine tumours (Ö berg et al 2013), this pathway being inhibited by somatostatin analogues (Villaume et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1) [12,13]. There are 25 years of evidence that octreotide controls the symptoms of severe diarrhea and flushing in patients with carcinoid syndrome [14 -16] [3].…”
Section: Introductionmentioning
confidence: 99%
“…An attractive candidate is VEGF-A. mTOR inhibition reduced VEGF-A excretion by NET cell lines (11). Additionally, in renal cancer xenografts, sensitivity to mTOR inhibition correlated with reductions in tumor hypoxia-inducible factor 1a messenger RNA translation, VEGF-A expression, and angiogenesis (12).…”
mentioning
confidence: 99%